Prosthodontic management of generalized severe dental fluorosis using simultaneous arch technique and Hobo twin-stage concept of full mouth rehabilitation - Vijay Kumar; Harpreet Singh; Sophia Sharma (Wolters Kluwer Medknow Publications, 2013)
Treatment of severe generalized dental fluorosis with surface defects to rehabilitate esthetics, phonetics, and mastication require removal of unsupported and pitted enamel and/or dentine, reestablishment of centric relation with or without reestablishing vertical dimension of occlusion and fabrication of full mouth crown and bridge work. In this case full occlusal reconstruction was done using simultaneous arch technique and Hobo twin-stage procedure following reorganizing approach as generalized fluorosis led to severe structural defects, oblique facets because of anterior traumatic occlusion and multiple dental caries, which were otherwise not possible to be treated by direct restorations alone. Centric relation was also recorded at reestablished vertical dimension.